(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Hypocalcaemia (HC) is the most common complication after thyroid surgery in differentiated thyroid cancer and leads to a prolongation of the hospital stay. While risk factors for HC after total thyroidectomy (TE) are well investigated, only few studies have been published about HC risk factors after completion of thyroidectomy. Our aim was to identify potential risk factors for HC after completion of TE and to compare these incidences with figures from primary total TE. MATERIALS AND METHODS A retrospective cohort study was undertaken including patients undergoing completion of TE between 2002 and 2013 in our tertiary care centre. Patients with hypocalcaemia (group 1) after undergoing second surgery were compared to normocalcaemia patients (group 2) with respect to gender, age, type of thyroid cancer, time interval between surgeries, pre/postoperative calcium and parathyroid hormone (PTH) levels, clinical hypocalcaemia signs and calcium substitution (intravenous, oral). Hypocalcaemia was defined as <2.10 mmol/l, hypoparathyroidism as <15pg/ml. RESULTS 34 (25 female, 9 male) patients were included. A total of 12 patients (33%) developed a hypocalcaemia (group 1). Three patients out of these also presented with hypoparathyroidism. One patient in each group showed clinical signs of hypocalcaemia. Calcium substitution was necessary in six cases in group 1 and in one case in group 2. There was a significant difference between the groups concerning postoperative PTH (25.1 vs 37.6 pg/ml) and calcium levels (1.87 vs 2.27 mmol/l) (p <0.05). Group comparison shows no significant relationships between all other parameters (age, gender, type of thyroid cancer and duration of interval between surgeries). Logistic regression analysis identified a low preoperative serum calcium level as the only dominant factor indicating postoperative hypocalcaemia. CONCLUSIONS A hypocalcaemia rate of 33% (12/34) and a hypoparathyroidism rate of 9% (3/34) after completion of thyroidectomy in our cohort is comparable to primary total thyroidectomy. A low preoperative calcium level is a significant risk factor for postoperative hypocalcaemia after completion of thyroidectomy. The prediction of hypocalcaemia still remains difficult since it has multifactorial causes.